2022
DOI: 10.1088/1741-2552/ac50bf
|View full text |Cite
|
Sign up to set email alerts
|

Impact of electrode position on the dynamic range of a human auditory nerve fiber

Abstract: Objective. Electrodes of a cochlear implant generate spikes in auditory nerve fibers (ANFs). While the insertion depth of each of the electrodes is linked to a frequency section of the acoustic signal, the amplitude of the stimulating pulses controls the loudness of the related frequency band. However, in comparison to acoustic stimulation the dynamic range of an electrically stimulated ANF is quite small. Approach. The dynamic range of an electrically stimulated ANF is defined as the interval of stimulus ampl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…More details are found in Table 3 . Our starting value of knoise = 0.00125 was from a previous study that fits reported RS values of feline auditory nerve fibers [ 24 ]. The upper part of Table 3 demonstrates that the CRRSS model needs about 10-fold knoise values of HH10 for similar RS and, second, the chosen knoise (0.00125) in the HH10 model leads to a significantly larger RS compared to Verveen’s data.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…More details are found in Table 3 . Our starting value of knoise = 0.00125 was from a previous study that fits reported RS values of feline auditory nerve fibers [ 24 ]. The upper part of Table 3 demonstrates that the CRRSS model needs about 10-fold knoise values of HH10 for similar RS and, second, the chosen knoise (0.00125) in the HH10 model leads to a significantly larger RS compared to Verveen’s data.…”
Section: Resultsmentioning
confidence: 99%
“…In order to show the impact of ion current fluctuations we have investigated the loudness discrimination with cochlear implants in a forthcoming study using a combined HH1 and HH10 model [ 24 ]. As mentioned above, the diameter of an auditory nerve fiber is much smaller in its peripheral part than after the soma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our model, auditory nerve fibers had an assumed smooth trajectory from the basilar membrane to the modiolus, a fixed length, and regular spacing, simply because the µ-CT images are not able to capture the trajectory of individual fibers. In the human cochlea, the fibers are bundled after passing the Organ of Corti through the basilar membrane (Cakir et al, 2019;Rattay and Tanzer, 2022). The actual trajectories of these fibers can vary considerably along the turns of the cochlea.…”
Section: Trajectory Of the Auditory Nerve Fibersmentioning
confidence: 99%